The Problem of the Motion of Bodies : A Historical View of the Development of Classical Mechanics - Capecchi, Danilo (2014)
This book focuses on the way in which the problem of the motion of bodies has been viewed and approached over the course of human history. It is not another traditional history of mechanics but rather aims to enable the reader to fully understand the deeper ideas that inspired men, first in attempting to understand the mechanisms of motion and then in formulating theories with predictive as well as explanatory value. Given this objective, certain parts of the history of mechanics are neglected, such as fluid mechanics, statics, and astronomy after Newton. On the other hand, due attention is paid, for example, to the history of thermodynamics, which has its own particular point of view on motion. Inspired in part by historical epistemology, the book examines the various views and theories of a given historical period (synchronic analysis) and then makes comparisons between different periods (diachronic analysis). In each period, one or two of the most meaningful contributions are selected for particular attention, instead of presenting a long inventory of scientific achievements.
Keywords: Mechanical engineering; Mechanics, Applied; Mechanics; Physics; Theoretical and Applied Mechanics; History and Philosophical Foundations of Physics; Mechanical Engineering